Hepatic enzyme concentrations as indicators of nonalcoholic fatty liver disease - Alvina, Alvina (Universa Medicina, 2009)
Nonalcoholic fatty liver disease (NAFLD) has emerged as a world-wide problem because it runs an asymptomatic course, ultimately leading to cirrhosis of the liver and portal hypertension, resulting in death. The prevalence of the disease accounts for 3-24% of the population in several countries. Generally there are increased concentrations of hepatic enzymes as markers of liver damage, such as serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT) and gamma glutamyl transferase (GGT). The aim of the present study was to determine the concentrations of hepatic enzymes as markers of NAFLD. The study design was cross-sectional, involving 90 subjects meeting the inclusion and exclusion criteria. The degree of severity NAFLD was determined by ultrasonography and the concentrations of SGOT, SGPT and GGT by automated clinical chemistry analyzer. The results indicated that there were 32 subjects with mild NAFLD (35.6%), 35 subjects with moderate NAFLD (38.9%) and 23 subjects with severe NAFLD (25.6%). There was a significant difference in degree of NAFLD by gender (p<0.05), where severe NAFLD was more frequent in males than in females. Concentrations of SGOT, SGPT and GGT were significantly different between degrees of NAFLD (p<0.05). The conclusion is that SGOT, SGPT and GGT concentrations are indicators of degree of NAFLD.